Integrated cave stability assessment: a case study at Naga Mas Cave, Mount Pua, Kinta Valley, Ipoh, Perak, Malaysia - Goh, Thian Lai; Lok, Kah Kit; Azimah Hussin,; Ailie Sofyiana Serasa,; Abdul Ghani Rafek,; Lee, Khai Ern; Tuan Rusli Mohamed,; Shao, Lei; Chen, Yanlong; Zhang, Mingwei (Penerbit Universiti Kebangsaan Malaysia, 2019)
Naga Mas Cave, a natural cave which also houses a temple is becoming one of the popular places of worship for Buddhist community in Ipoh, Perak. With the increasing number of worshippers entering the cave, the stability of this cave becomes important. With that in mind, an assessment on natural cave stability was conducted in the interest of public safety. Slope Mass Rating (SMR), Q rock mass classification system and cave roof thickness-width ratio of cave were employed in this assessment. The lithology of study area consists of dolomitic limestone. Discontinuity surveys were conducted at two slopes, labeled C1 and C2. For slope C1, three (3) joint sets J1, J2 and J3 with the dip direction and angles of 332º/49º, 154º/37º and 049º/80º, respectively, were identified. While slope C2 has four (4) sets of joints J1, J2, J3 and J4 with the dip direction and angles of 323º/44º, 125º/57º, 42º/76º, 263º/67º, respectively. The relationship between the rock quality, Q values and cave width shows that all parts inside the cave need support except for the cave chamber at the northern part. As for the cave wall stability, the northern part of the south east wall, south eastern and southern part as well as the north western wall and south western corner were classified as poor slope class due to the unfavorable orientation of the cave wall. Ratio of cave roof thickness and cave width shows that the cave is stable. From the results, a mitigation plan is proposed to highlight the cave safety zone to ensure the safety of worshippers and public visiting the cave.